2017
DOI: 10.3390/molecules23010025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Genes Involved in Anthocyanin Biosynthesis in Red and Green Walnut (Juglans regia L.)

Abstract: Fruit color is an important economic trait. The color of red walnut cultivars is mainly attributed to anthocyanins. The aim of this study was to explore the differences in the molecular mechanism of leaf and peel color change between red and green walnut. A reference transcriptome of walnut was sequenced and annotated to identify genes related to fruit color at the ripening stage. More than 290 million high-quality reads were assembled into 39,411 genes using a combined assembly strategy. Using Illumina digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 82 publications
1
36
0
Order By: Relevance
“…In genotypes with red leaves, the red colour is associated with the production of anthocyanins, a soluble pigment class 10,21 . Anthocyanins confer an enhanced photoprotection from excess solar irradiation in several plant species 16,22 , as already has been observed in P. cerasifera, Jathropha curcas, Juglans regia and Ocimum basilicum 10,[23][24][25] . When studying ontogenetic differences between green and anthocyanin-rich leaves, the ideal strategy is using isogenic lines for this character, in order to exclude differences related to the genetic background.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…In genotypes with red leaves, the red colour is associated with the production of anthocyanins, a soluble pigment class 10,21 . Anthocyanins confer an enhanced photoprotection from excess solar irradiation in several plant species 16,22 , as already has been observed in P. cerasifera, Jathropha curcas, Juglans regia and Ocimum basilicum 10,[23][24][25] . When studying ontogenetic differences between green and anthocyanin-rich leaves, the ideal strategy is using isogenic lines for this character, in order to exclude differences related to the genetic background.…”
supporting
confidence: 61%
“…For this reason, several studies compare two cultivars of the same species differing in leaf colour phenotype 10 . Other differences between red and green leaves have been detected for leaf thickness 21,26 , wax formation, flavonoid production, sugar translocation 10,27 and transcription factor activities of MYB and WD40 families 23,25 .…”
mentioning
confidence: 99%
“…This partially explains the decreased retention rate of flavonoid in the shell pigment ( Figure 1A). Given that previous studies have not detected anthocyanin in walnut green husk [28], we assumed that the high retention rate of flavonoids in husk pigment was due to high-molecular-weight flavonoids. At different digestion phases and in the dialysis bags, the flavonoid retention rate was characterized as follows: EH > NEH > CH, which demonstrated that the enzyme along with acid or alkaline substances positively influenced flavonoid release and absorption, with the enzyme showing superior effect.…”
Section: Comparative Analysis Of Flavonoid Retentionmentioning
confidence: 99%
“…), FLOWERING LOCUS T1 ( FT1 ) and FLOWERING LOCUS T2 ( FT2 ) coordinate the repeated cycles of vegetative and reproductive growth, revealing that in response to winter temperatures, FT1 determines reproductive onset, whereas FT2 responds to warm temperatures and long days in the growing season and promotes vegetative growth and inhibition of bud set. Li et al [ 31 ] explored the differences of leaf and peel color change between red and green walnut by transcriptome analysis and identified 3083 differentially expressed genes (DEGs) between red and green walnut peel at the ripening stage. Ma et al [ 32 ] investigated the effects of low-temperature treatment on stamen petaloidy in rose ( Rosa hybrida ) and revealed that low temperatures increase petal number, at least to some extent.…”
Section: Introductionmentioning
confidence: 99%